Internal Rotation in Propionic Acid: Near-Infrared-Induced Isomerization in Solid Argon - Maçôas, Ermelinda M. S. (2005)
The conformational system of propionic acid (CH3CH2COOH) is studied in solid argon. It is predicted by the ab initio calculations that this molecule has four stable conformers. These four structures are denoted Tt, Tg±, Ct, and Cg±, and they differ by the arrangement around the C−O and Cα−C bonds. The ground-state Tt conformer is the only form present at 8 K after deposition of an argon matrix containing propionic acid. For the CH3CH2COOH and CH3CH2COOD isotopologues, narrow-band excitation of the first hydroxyl stretching overtone of the conformational ground state promotes the Cα−C and C−O internal rotations producing the Tg± and Ct conformers, respectively. A subsequent vibrational excitation of the produced Tg± form induces its conversion to the Cg± conformer by rotation around the C−O bond. In the dark, all of the produced conformers decay to the conformational ground state at different rates. The decay kinetics and its temperature dependence allow the identification of the conformers by IR absorption spectroscopy, which is supported by ab initio calculations of their vibrational spectra. For the CH3CH2COOD isotopologue, the excitation of molecules isolated in different matrix sites results in site-dependent photoisomerization rates for the Cα−C and C−O internal rotations, which also confirm the identification of the photoproducts.